2021
DOI: 10.1128/msphere.00162-21
|View full text |Cite
|
Sign up to set email alerts
|

Dental Plaque Microbial Resistomes of Periodontal Health and Disease and Their Changes after Scaling and Root Planing Therapy

Abstract: The emergence and development of resistance to antibiotics in periodontal pathogens have affected the success rate of treatment for periodontitis. The development of new antibacterial strategies is urgently needed to help control and treat periodontal disease, and dental plaque microbiome studies offer a promising new angle of attack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 84 publications
1
15
0
Order By: Relevance
“…Other studies have shown that clinical improvement post SRP was accompanied by changes in the subgingival microbiota (Haffajee et al, 1997; Feres et al, 2020) and reduction in members of the red complex (Belstrøm et al, 2018; Kang et al, 2021). We did not observe a decrease in those organisms after treatment; it may be because, in our case, we were measuring the active community and not just the metagenome.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have shown that clinical improvement post SRP was accompanied by changes in the subgingival microbiota (Haffajee et al, 1997; Feres et al, 2020) and reduction in members of the red complex (Belstrøm et al, 2018; Kang et al, 2021). We did not observe a decrease in those organisms after treatment; it may be because, in our case, we were measuring the active community and not just the metagenome.…”
Section: Discussionmentioning
confidence: 95%
“…With this background, it is pertinent to emphasize that a current investigation denoted that antimicrobial-resistance genes were perceived in the plaque of more than 50% of healthy persons [ 45 ]. This aspect can partially elucidate the decreasing efficacy of the antimicrobials implemented clinically [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…AA induces an inhibition zone on periodonpathogenic bacterial cultures ( Saini et al, 2008 , Tambekar et al, 2009 ) and suppresses P. gingivalis and P. intermedia ( Clark et al, 1993 ). A recent genetic analysis has revealed emerging antibiotic-resistant genes (ARGs) and metal-resistant genes (MRGs) in the dental plaque microbiota after scaling and root planing, thus highlighting the need for novel antibacterial strategies to control periodontitis ( Kang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%